THE ARTISTIC BRAND: A BIBLIOMETRIC ANALYSIS OF VISUAL AND PERFORMING ARTS IN BRANDING STRATEGIES - Divya.H; Joseph, Melby; Thomas, Ambili Catherine; John, Sherin Elizabeth; Zacharia, Alan; Mathew, Prageesh C (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This bibliometric analysis investigates the role of visual and performing arts in branding, focusing on the strategic use of artistic elements such as design, imagery, music, theater, and dance to enhance brand identity, consumer engagement, and value communication. Data for the study were sourced from the Scopus database, covering 149 documents published between 1995 and 2023. Using Biblioshiny and VOSviewer, the analysis provides insights into annual scientific production trends, identifying a steady increase in research output, particularly in recent years. The study highlights the most relevant authors and sources, with contributions from multidisciplinary journals and a balanced distribution of authorship. A Three-Field Plot reveals the interconnected relationships between authors, publication sources, and their countries, demonstrating strong Western representation and emerging global participation. Trend topics such as "branding," "performing arts," and "visual arts" are identified as central themes driving research, while the thematic map categorizes keywords into Motor, Basic, Niche, and Emerging Themes, offering a structured overview of the field. Bibliographic coupling of documents uncovers clusters of influential works and shared references, showcasing the foundational literature and methodological alignments. Additionally, the co-occurrence of keywords highlights six thematic clusters, bridging cultural, artistic, and commercial domains in branding. The findings underscore the interdisciplinary nature of the field and its evolving priorities, emphasizing the potential for cross-cultural and creative innovations. Practical implications suggest that integrating visual and performing arts in branding strategies can foster emotional connections and cultural relevance. Future research should explore underdeveloped themes and expand international collaboration to enrich the discourse further.